Flood governance: A review on allocation of flood victims using location-allocation model and disaster management in Malaysia - Noridayu, Mah Hashim; Noor Akma, Abu Bakar; Zetty Ain, Kamaruzzaman; Sarifah Radiah, Shariff; Siti Nur Zahrah, Amin Burhanuddin (Universiti Malaysia Pahang, 2023)
Flood management can be defined as the technique and strategy to reduce the risk and damage from flooding. The efficient strategies for the both short-term and long-term plans is needed in order to minimise losses and damage during disaster happen. Flood governance entails the need of a coordinated system in dealing with this natural disaster. The phases of the flood disaster management cycle such as flood preparedness, flood mitigation, Emergency Response Plan (ERP), and flood recovery helped the federal government and states government to overcome the flood disaster. In Malaysia, the disaster management undergoes three levels, where each level is governed by a committee with specified responsibilities. Flood disaster mitigation is crucial since it is possible to prevent damage that is brought upon by flood disaster. During the flood event, all the flood victims must be allocated to relief center. The allocation process needs to be conducted efficiently to avoid much worse incidents happening. The aims of this paper review are to explore the existing knowledge on flood mitigation and to identify Location-allocation model currently applied to solve allocation of flood victims to relief centre.The paper review is based on secondary data to give comparison and recommendation in achieving the objective. However, lack of coordination remains an issue that could potentially be tackled using a more efficient framework. Further researches are needed to test the effectiveness of this framework in improving flood governance.